2019
DOI: 10.3389/fnins.2019.00634
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Whole Brain Temporal Variation of Functional Connectivity via Zero and First Order Derivatives of Sliding Window Correlations

Abstract: Brain functional connectivity has been shown to change over time during resting state fMRI experiments. Close examination of temporal changes have revealed a small set of whole-brain connectivity patterns called dynamic states. Dynamic functional network connectivity (dFNC) studies have demonstrated that it is possible to replicate the dynamic states across several resting state experiments. However, estimation of states and their temporal dynamicity still suffers from noisy and imperfect estimations. In regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…In addition to these observations; the results of our study may provide a new clue to the functional impairment in patients with PS; in terms of whole-brain functional network connectivity. The same finding that patients had a longer duration in the sparsely connected state also has been reported in multiple brain diseases, such as depressive disorders( Zhi et al, 2018 , Wang et al, 2020 ), schizophrenia( Yu et al, 2015 , Rabany et al, 2019 , Espinoza et al, 2019 ), Huntington's disease( Espinoza et al, 2019 , Espinoza et al, 2019 ); and neurofibromatosis( Mennigen et al, 2019 , Mennigen et al, 2019 ). Given the above research, such abnormalities in dFNC may be the underlying mechanism of similar dysfunctions in different brain disorders.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to these observations; the results of our study may provide a new clue to the functional impairment in patients with PS; in terms of whole-brain functional network connectivity. The same finding that patients had a longer duration in the sparsely connected state also has been reported in multiple brain diseases, such as depressive disorders( Zhi et al, 2018 , Wang et al, 2020 ), schizophrenia( Yu et al, 2015 , Rabany et al, 2019 , Espinoza et al, 2019 ), Huntington's disease( Espinoza et al, 2019 , Espinoza et al, 2019 ); and neurofibromatosis( Mennigen et al, 2019 , Mennigen et al, 2019 ). Given the above research, such abnormalities in dFNC may be the underlying mechanism of similar dysfunctions in different brain disorders.…”
Section: Discussionsupporting
confidence: 75%
“…First, the functional chronnectome was investigated not only by focusing on component functional connectivity at certain points in time, but also from a first-order-derivative-perspective, which encompasses the changes of connectivity between two consecutive windows (‘speed’ of connectivity change; ( Calhoun et al, 2014 , Espinoza et al, 2019 ). It has been shown that including these first order derivatives facilitates the estimation of the optimal number of dynamic brain states, and ultimately results in a higher sensitivity of finding neuropsychiatric disease-related patterns ( Espinoza et al, 2019 ). Second, by including derivatives we demonstrated that dynamic brain states seem to adhere to specific transition sequences, called attractors, with dynamic connectivity increasing and decreasing in orbiting patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Successive windows were shifted in steps of 1 TR each, which means that windows are overlapping. Subsequently, average sliding window correlations (ASWC; window size = 25 TR) and the first order derivatives were calculated for every subject, resulting in 175 windows per subject, with each window containing 1378 × 2 = 2756 values ( Espinoza et al, 2019 , Vergara et al, 2019a ). We opted for the ASWC approach, as this requires smaller window lengths, and thus a more accurate estimation of dFC, by reducing spurious fluctuations, as compared to the standard sliding window correlation approach ( Vergara et al, 2019a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, k‐means clustering was performed (maximum iterations of 4,000, correlation distance method, 33 replicates) using both the ASWC as well as their first derivatives of all subjects (derivatives were normalized for every subject to match the variance of the correlations). Including the first derivatives has been shown to result in higher sensitivity for capturing group‐differences in dynamic FNC (Espinoza et al, ). To estimate the optimal number of clusters (k), the following cluster validity indexes were computed for a range of k (1–10) using GIFT: Elbow method, Bayesian information criterion (BIC), Dunn's index, Gap statistic, Akaike information criterion (AIC), and Silhouette method (Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%